Deerproofing Your Yard & Garden - Massingham, Rhonda 1959- (North Adams, MA : Storey Pub., 2005)
Describes techniques and strategies to prevent and deter deer from invading yards and gardens; and discusses plants that repel deer, the health risks that come with the presence of deer, and other related topics.
Keywords: Deer -- Control; Wildlife pests -- Control